THE IMPACT OF THE COVID-19 PANDEMIC ON STROKE PATIENTS: A NARRATIVE LITERATURE REVIEW - Liliana Chaves (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
In December 2019, the China Popular Republic informed the world that an outbreak caused by a highly contagious coronavirus, capable of developing severe cases of bilateral pneumonia, had been detected. The disease spread throughout the world and, in March 2020, the World Health Organization considered it a pandemic. Since social isolation measures have been instituted in various parts of the world, it was considered urgent to reflect on the impact of the COVID-19 pandemic on stroke patients to obtain some important subsidies for the future. Therefore, a narrative literature review was carried out and it was found that the state of the art reveals that there was a significant decrease in stroke patients admitted to hospital units, as well as a decrease in consultations, health education sessions and treatments, including rehabilitation, which is particularly worrying in a population that has already shown a high rate of unmet needs.